Murder, she wrote [large type] : close-up on murder : a murder, she wrote mystery - Bain, Donald, 1935-2017 (Fletcher, Jessica. Murder, she wrote., 2015)
Cabot Cove is about to be invaded - by Hollywood. One of Jessica's older novels is being made into a big-budget movie. The producer has decided to shoot most of the film on location in town, since the book was loosely based on a murder that shocked Cabot Cove over a decade earlier. The murder occurred when a judge was gunned down while walking her dog. The prime suspect: an enraged husband whom the judge ruled against in a child custody case. But further investigation pointed to the victim's own husband - and ultimately to his mistress, accused of eliminating her rival. Unfortunately, everyone on the set has a hidden agenda. A novice director wants his shot at the big-time. A fading star, making a comeback, has many unreasonable demands. Her astrologer sees trouble in the stars. And a stranger on the movie lot is stalking Jessica. But fiction and reality fatally collide when the actress playing the judge is shot - the only witness her dog - and there's a cast and crew of possible suspects. With tensions between locals and the Hollywood horde mounting, Jessica must find the killer before anyone else is left on the cutting-room floor.